2011
DOI: 10.1002/ejic.201100981
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Reactivity of Ester‐Functionalized 5‐Membered RhI‐κ2‐C,O‐Chelates and Their Relevance in Rh(cod)‐Mediated Carbene Polymerization

Abstract: The previous mechanistic studies of the Rh-mediated polymerization of carbenes suggests the involvement of organometallic compounds that have been derived from Rh(diene) species that contain a five-membered chelate ring of the type Rh{κ 2 -C,O-[-CH(COOR)-CH(Pol)-C(OR)=O-]} (Pol = polymer chain), which are characterized by the coordination of the β-ester group of the growing polymer chain to the metal. Herein we present our efforts to characterize the possibly related Rh I (cod){κ 2 -C,O-[-CH(COOR)-CHRЈ-C(OR)=O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 49 publications
0
14
0
Order By: Relevance
“…1,5-cyclooctadiene (cod) derivatives) under the applied reaction conditions. 267,277,279 These findings are expected to lead to future improvements of this approach in terms of yields, initiation efficiencies of the catalysts and in the synthesis of stereoregular polymers with different tacticities. This clearly indicates that this new reaction has not yet been exploited at its full potential.…”
Section: Scheme 49 Migratory Insertion Of Carbenesmentioning
confidence: 92%
See 1 more Smart Citation
“…1,5-cyclooctadiene (cod) derivatives) under the applied reaction conditions. 267,277,279 These findings are expected to lead to future improvements of this approach in terms of yields, initiation efficiencies of the catalysts and in the synthesis of stereoregular polymers with different tacticities. This clearly indicates that this new reaction has not yet been exploited at its full potential.…”
Section: Scheme 49 Migratory Insertion Of Carbenesmentioning
confidence: 92%
“…266 The reaction proceeds via a migratory insertion mechanism (Scheme 55) 266 and no or little chain transfer seems to occur. [275][276][277][278] Most recently, detailed mechanistic studies revealed that the active species responsible for this polymerisation is a Rh III (allyl)(alkyl) species (Fig. 7) that can be formed by modifications of rather simple Rh I (diene) precursors (e.g.…”
Section: Scheme 49 Migratory Insertion Of Carbenesmentioning
confidence: 99%
“…This is in agreement with previously-described chain transfer/ termination pathways. 50,58 The polymer yield drops upon incorporation of ethene as compared to the yields obtained in the carbene homopolymerisation reactions. Previous studies on the EDA homopolymerisation revealed that chain transfer occurs only to a very limited extent.…”
Section: Olefin-carbene Copolymerizationsmentioning
confidence: 99%
“…[29][30][31][32][33][34][35][36][37][38][39][40][41][42] Highly stereospecific (co)polymerisation of diazoesters (N 2 CHCOOR) can be achieved in good yields and with high M w in a Rh catalysed process. 30,[43][44][45][46][47][48][49][50][51] This leads to the formation of syndiotactic polymers bearing an ester functionality at every single carbon atom of the polymer main chain.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we have shown that highly stereospecific polymerization of polar monomers can be achieved in good yields and with high M w by Rh-catalyzed (co)polymerization of diazoesters (N 2 CHCOOR). , This leads to the formation of syndiotactic polymers bearing an ester functionality at every single carbon atom of the polymer main chain via a coordination/insertion mechanism (Scheme ).…”
Section: Introductionmentioning
confidence: 99%